In vitro and in vivo peppermint (Mentha piperita) growth promotion by nonmycorrhizal fungal colonization - Mucciarelli, Marco (The New phytologist, 2003)
•  Here peppermint growth and terpene production of in vitro generated plants (Mentha piperita) in response to inoculation with a leaf fungal endophyte were characterized. •  Peppermint plants were studied by means of morphometric, biochemical and image analysis, employing both in vitro and in pot cultures. Leaf essential oils were analysed by gascromatography-mass spectrometry. •  The endophyte induced profound effects on the growth of peppermint, which responded with taller plants bearing more expanded leaves. The observed increase of leaf dry matter over leaf area suggested a real improvement of peppermint metabolic and photosynthetic apparatus. Root architecture was of the herring-bone type, showing greater dry biomass percentage over the total. A sustained lowering of (+)-menthofuran and an increase of (+)-menthol percentage concentrations were found in plants from both in vitro and pot cultures. •  The study represents the first report on specialized endophytic fungi in peppermint green tissues and highlights some of the principal morphological and biochemical aspects of this mutualism. Effects exerted on plant growth and essential oil production in peppermint suggest further biotechnological applications